Beswick Aboriginal Reserve - Northern Territory Administration. Welfare Branch ([Darwin] : Welfare Branch, 1966)
History, facilities, services and population of the Beswick Aboriginal Reserve in the Northern Territory, in the late 1960's.
Cover title.
Keywords: Aboriginal Australians -- Northern Territory -- Beswick -- Reserves; Settlement and contacts - Government settlements, reserves; Social welfare - Government; Beswick Aboriginal Reserve (N.T.); Wugularr / Beswick (NT Top End Upper Roper SD53-09)